Ecological Implications of Changes in the Arctic Cryosphere - Vincent, Warwick F.; Callaghan, Terry V.; Dahl-Jensen, Dorthe; Johansson, Margareta; Kovacs, Kit M.; Michel, Christine; Prowse, Terry; Reist, James D.; Sharp, Martin (AMBIO, 2011)
Snow, water, ice, and permafrost are showing evidence of substantial change in the Arctic, with large variations among different geographical areas. As a result of these changes, some habitats and their associated ecosystems are expanding, while others are undergoing rapid contraction. The warming of the Arctic cryosphere is limiting the range for cold-adapted biota, and less specialized taxa including invasive species from the south are likely to become increasingly common. Extreme climate events such as winter thawing are likely to become more frequent, and may accelerate shifts in community structure and processes. Many Arctic ecosystems are interdependent, and changes in the cryosphere are altering physical, biogeochemical, and biological linkages, as well as causing positive feedback effects on atmospheric warming. All of these climate-related effects are compounded by rapid socio-economic development in the North, creating additional challenges for northern communities and indigenous lifestyles that depend on Arctic ecosystem services.